1980
DOI: 10.1172/jci109868
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreconstitution by Peripheral Blood Leukocytes in Adenosine Deaminase-deficient Severe Combined Immunodeficiency

Abstract: A B S T R A C T Transplantation of histocompatible al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 25 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Even so, the ability to collect hematopoietic stem cells by a less morbid procedure might be ofuse in allogeneic settings for donors who are unwilling to submit to an operative procedure. This point was recently demonstrated by Rich et al (9) in a case report involving immune reconstitution with allogeneic peripheral blood leukocytes in the setting of adenosine deaminase-deficient severe combined immuno-deficiency. In this report the donor (the patient's father) refused to be a bone marrow donor, but consented to leukopheresis.…”
mentioning
confidence: 62%
“…Even so, the ability to collect hematopoietic stem cells by a less morbid procedure might be ofuse in allogeneic settings for donors who are unwilling to submit to an operative procedure. This point was recently demonstrated by Rich et al (9) in a case report involving immune reconstitution with allogeneic peripheral blood leukocytes in the setting of adenosine deaminase-deficient severe combined immuno-deficiency. In this report the donor (the patient's father) refused to be a bone marrow donor, but consented to leukopheresis.…”
mentioning
confidence: 62%
“…As in dogs, myelosuppressive chemotherapy may induce an overshoot of circulating committed progenitors-and, by implication, of more primitive stem cellsfollowing an initial nadir. Thus, a mean fourfold increase in circulating CFU-GM was seen in nine of fourteen patients with solid tumours being treated with adriamycin and cyclophosphamide (Richman et al, 1976) and up to 25-fold increases have been observed following induction and consolidation treatment for acute non-lymphocytic leukaemia (ANLL). There are, however, early indications that these increases in circulating CFU-GM numbers may not be accompanied by equivalent increases in the numbers of more primitive progenitor cells.…”
Section: Collection Of Cscmentioning
confidence: 99%
“…Prospective donors may occasionally refuse to donate bone marrow, opting instead to contribute peripheral blood (Rich et al, 1980). This alternative is likely to be exercised much more frequently by unrelated (non-family member) donors who may be used with increasing frequency in the future (Hansen et al, 1980).…”
Section: Engraftment With Peripheral Blood Cellsmentioning
confidence: 99%